Hydrogenation of levulinic acid to gamma-valerolactone over nickel supported organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Catalysis Today, 2023)
In this work, a series of Ni/Organoclay catalysts with different Nickel loadings were prepared by the wetimpregnation method for the catalytic hydrogenation of levulinic acid (LA) to gamma-valerolactone (GVL). Reaction parameters such as reaction temperature, pressure, solvent effect, and wt% of catalyst were optimized to get excellent conversion of levulinic acid selectively to gamma-valerolactone. Ni/Organoclay with 30% Nickel loading exhibited 100% conversion of LA with 100% selectivity towards GVL at 140 degrees C and 3.0 MPa H2 pressure using 1,4-dioxane as a solvent in 5 h. Different bulk and surface characterization techniques such as XRD, BET, FE-SEM, HR-TEM, XPS, XRF, NH3-TPD, and H2-Chemisorption were used to characterize the Ni/Organoclay catalyst. BET and NH3-TPD analysis showed that the pre-treatment of bentonite with surfactant (CTAB) improved the pore volume, surface area, and acidity of Organoclay which assisted in improving the conversion and selectivity of LA and GVL respectively.
Keywords: ?-Valerolactone (GVL); Bentonite; Hydrogenation; Levulinic acid (LA); Nickel; organoclay